A high-efficiency multidirectional wind energy harvester based on impact effect for self-powered wireless sensors in the grid. (9th October 2019) - Tang, Minfeng; Guan, Qihui; Wu, Xiaoping; Zeng, Xiaohui; Zhang, Zutao; Yuan, Yanping
Abstract: In the smart grid, several wireless sensors for status monitoring have energy supply problems that hinders the development of smart grids, so self-powered wireless sensors that harvest ambient energy for their energy supply have been proposed. The collection of environmental energy using piezoelectric materials, such as Polyvinylidene Fluoride (PVDF) film, to power wireless sensors has generated significant interest. In this paper, we propose a novel wind energy harvester (WEH) using a wind vane and PVDF film to convert the multidirectional wind energy in the grid into electricity. The high-efficiency energy system consists of four main components: the multidirectional wind collection module, the deformation amplification module, the electricity generator module and the power storage module. The multidirectional wind collection module ensures the PVDF film remains in the maximum windward area. The deformation of the PVDF film is amplified by the impact stick. The electricity generator module transforms wind energy into electricity. The power storage module stores the electricity in supercapacitors to supply energy to wireless sensors in the grid. The proposed system is demonstrated through simulation and bench tests, which can show that output power of one unit with impact can achieve 46.2 mW at 6.5 m s −1 wind speed, demonstrating the feasibility and efficiency of the proposed WEH system for application in self-powered wireless sensors in the grid.